Comunicação e Covid-19: um estudo de caso da assessoria de comunicação da secretaria de estado da saúde do Espírito Santo no ano de 2020 - Côrtes, Thaísa Guimarães (2025)
This research in the field of Communication and Health and Risk Communication has as its main objective to understand how the Communications Advisory Office of the Health Department of the Government of Espírito Santo positioned itself in the face of the COVID-19 pandemic through the creation of risk communication strategies in 2020. The aim was to understand which risk communication strategies aimed at health were worked on that year and how they were presented. During its development, it was decided to establish that the empirical work would collect quantitative and qualitative information, through the analysis of the titles published on the Sesa website in 2020, through the press conferences made available on the department's official YouTube channel and through semi-structured interviews with Communications and Health professionals who worked that year helping to build communication strategies. To this end, the research consisted of collecting data from a sample containing 244 titles, four press conferences lasting more than 3 hours and interviews totaling more than 6 hours of conversation. To this end, the first phase of the research was a bibliographical survey on the subject. Next, information was gathered about the COVID-19 scenario, both epidemiological and regulatory publications, in order to elucidate the context experienced that year, and finally to collect the data. The data were processed and analyzed to carry out a triangulation of methods and the construction-synthesis, seeking to understand which risk communication strategies focused on health were present. Through the construction synthesis, it was found that not all strategies are based on what the concept of Risk Communication proposes, especially the strategies recommended by the World Health Organization (WHO) and the Pan American Health Organization (PAHO), although some principles are present.